Polygonatum polysaccharides as gut microbiota modulators: implications for autophagy-dependent PD-L1 clearance in cancer immunotherapy - Li, Yongjie; Jiang, Feng; Wang, Ting; Zeng, Min (Frontiers in Nutrition, 2025)
The purpose of this review article is to examine the biotransformation of Polygonatum polysaccharides and the role that gut microbiota plays in that biotransformation. In the past years, PD-L1 has come under much attention as an immune checkpoint target and autophagy-lysosomal mediated degradation of PD-L1 provides new approaches for cancer immunotherapy. This review explores how gut microbiota-mediated biotransformation of Polygonatum polysaccharides may influence PD-L1 expression and degradation, potentially offering a novel approach to enhancing cancer immunotherapy. This synthesis of information highlights the complex relationship between foods, microbiota, and the immune system and supports the emerging idea that targeting microbiota-mediated metabolism and the immune response may be beneficial to improve cancer therapeutics.